Low humoral and cellular immune responses early after breakthrough infection may contribute to severe COVID-19 - Lee, Chan Mi; Choe, Pyoeng Gyun; Kang, Chang Kyung; Lee, Eunyoung; Song, Kyoung-Ho; Bang, Ji Hwan; Kim, Eu Suk; Kim, Hong Bin; Kim, Nam Joong; Kim, Hang-Rae; Kim, Youngju; Lee, Chang-Han; et al. (Frontiers in Immunology, 2023)
Background: Little is known about the immune determinants for severe coronavirus disease 2019 (COVID-19) in individuals vaccinated against severe acute respiratory syndrome coronavirus 2. We therefore attempted to identify differences in humoral and cellular immune responses between patients with non-severe and severe breakthrough COVID-19. Methods: We prospectively enrolled hospitalized patients with breakthrough COVID-19 (severe and non-severe groups) and uninfected individuals who were vaccinated at a similar time (control group). Severe cases were defined as those who required oxygen therapy while hospitalized. Enzyme-linked immunosorbent assays and flow cytometry were used to evaluate humoral and cellular immune responses, respectively. Results: Anti-S1 IgG titers were significantly lower in the severe group than in the non-severe group within 1 week of symptom onset and higher in the non-severe group than in the control group. Compared with the control group, the cellular immune response tended to be diminished in breakthrough cases, particularly in the severe group. In multivariate analysis, advanced age and low anti-S1 IgG titer were associated with severe breakthrough COVID-19. Conclusions: Severe breakthrough COVID-19 might be attributed by low humoral and cellular immune responses early after infection. In the vaccinated population, delayed humoral and cellular immune responses may contribute to severe breakthrough COVID-19.